PENGEMBANGAN DESAIN IDENTITAS VISUAL UNIKU SEBAGAI UPAYA PENJENAMAAN UNIVERSITAS - Herlina, Elin; Azhar Natsir Ahdiyat; Jerry D. Rahajaan (Universitas Swadaya Gunung Jati, 2025)
In the current era, universities face significant challenges in operating under increasingly commercial principles. One crucial aspect of addressing these challenges is branding, in which visual identity plays a key role. Universitas Kuningan (Uniku), as a private higher education institution in West Java, has established visual identity elements and has begun branding initiatives. However, inconsistencies in the use of emblem and variations in their application are still frequently observed. Therefore, Uniku needs to further develop its visual identity to enhance professionalism, consistency, and integration. This study aims to analyze the current state of Uniku’s visual identity and develop a more integrated, comprehensive, and branding-oriented visual identity design and system. The development process adopts Alina Wheeler’s Universal Identity Design Process approach. The study results in a range of design assets, including visual identity elements, brand collateral, and an identity system aligned with Uniku’s vision, mission, objectives, target audience, image, and persona. These developments serve as recommendations for the university in strengthening its branding efforts, positioning Uniku as a leading university by 2035. Keywords: Visual identity, brand, branding, university, Uniku